Calidad ambiental mediante la diversidad de avifauna acuática en el humedal La Segua - Varela Cevallos, Josselyn Estefanía (2019)
The objective of this research was to evaluate the environmental quality through the aquatic avifauna in the La Segua Wetland, it was carried out in San Antonio, La Sabana, Larrea and La Segua communities that make up the same, where the survey technique was used on a sample of the population of each community to determine the productive activities that are carried out in them, 38% of the respondents dedicate themselves to agriculture, 28% to home jobs, 12% to others (public works), 11% business, 3% livestock, fishing, aquaculture and 2% none. To determine the diversity of birdlife, Simpson, Shannon-Wiener and Pielou indices were applied, in addition to the richness where it was greater in the micro body habitat of water, followed by plains, aquatic vegetation and populated areas. The diversity was medium according to the Shannon and Pielou index, the latter is slightly heterogeneous in abundance, while the probability in relation to the Simpson dominance index is 0,70, with high diversity in relation to the dominant species Phalacrocorax brasilianus; based on this the environmental quality of the wetland was determined. La Segua, which had a value of 0.65, shows that this complex ecosystem is healthy above the "Average Environmental Quality", which assumes values where a minimum admissible state is expressed according to Batelle-Colombus.